The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1590/2237-6089-2015-0043
|View full text |Cite
|
Sign up to set email alerts
|

Effect of transcranial direct current stimulation (tDCS) over the prefrontal cortex combined with cognitive training for treating schizophrenia: a sham-controlled randomized clinical trial

Abstract: Introduction: We report a transcranial direct current stimulation (tDCS) protocol over the dorsolateral prefrontal cortex (DLPFC) combined with cognitive training in schizophrenia. Method:We assessed psychotic symptoms in nine patients using the Positive and Negative Syndrome Scale (PANSS). All evaluations were scored at baseline, at the end of the intervention protocol, and during a 4-week follow-up. The tDCS protocol consisted of 10 consecutive sessions over 5-day periods. We placed the cathode over the righ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(11 citation statements)
references
References 10 publications
(4 reference statements)
0
11
0
Order By: Relevance
“…The authors reported enhanced cognitive performance on word and picture N-back tasks and MCCB overall composite when CR was paired with tDCS. In a negative findings study ( 70 ), 10 patients were randomized to either active or sham tDCS (10 consecutive sessions over 5 days), with cognitive training (administration of n-back and sequence learning tasks) randomly applied during one of the tDCS sessions. The combined approach failed to improve clinical symptoms and cognitive performance.…”
Section: Review Of Physical Exercise and Tdcs Studiesmentioning
confidence: 99%
“…The authors reported enhanced cognitive performance on word and picture N-back tasks and MCCB overall composite when CR was paired with tDCS. In a negative findings study ( 70 ), 10 patients were randomized to either active or sham tDCS (10 consecutive sessions over 5 days), with cognitive training (administration of n-back and sequence learning tasks) randomly applied during one of the tDCS sessions. The combined approach failed to improve clinical symptoms and cognitive performance.…”
Section: Review Of Physical Exercise and Tdcs Studiesmentioning
confidence: 99%
“…The study was completed and the analysis carried out with 10 patients in each group. Referring to the pre‐assumptions of the covariance method, especially normality, and also to similar studies with similar sample sizes (Lotfi et al, ; Sayyah, Bagheri, Karimi, & Ghasemzadeh, ; Shiozawa et al, ), random selection of this sample size would be justifiable. The CBT, calcium supplement plus vitamin D, and mixed treatments were well tolerated and no serious event was observed during the study period.…”
Section: Resultsmentioning
confidence: 99%
“…37 Moreover, again, there was a different methodological aspect concerning the timing of stimulation sessions between the studies, which was more spaced in the first 37 and less spaced in the second study. 38 Finally, the third approach focused on anodal tDCS of the left DLPFC (F3) and catodal tDCS of the right orbitofrontal cortex (Fp2), which emphasizes the facilitation of the left DLPF. This is in line with the second approach, being considered of interest for the treatment of negative symptoms in SCZ.…”
Section: Discussionmentioning
confidence: 99%
“…Using the same electrode placement, Shiozawa et al 38 investigated the effect of the concomitant use of tDCS and cognitive training over clinical symptoms in a small sample of adult patients with SCZ (N = 10). All patients were using atypical antipsychotic medication.…”
Section: Summary Of Findingsmentioning
confidence: 99%